(untitled) (Journal of Economic Research & Business Administration, 2019)
Today, the main source of economic growth is the extraction of mineral oil, although in recent years there has been a significant increase in the role of consumer demand in the domestic market. In the context of globalization, the main indicator of the economy of oil-producing countries is oil prices. However, in a period of globalization, developing countries need not only energy, but also economic resources to develop their economic situation on the global market. Thus, establishing creditworthiness is the key to attracting foreign capital. The development of the stock market is not an indicator of the country’s stable creditworthiness. This study fills the required gap, verifying with the extent to which the development of the stock market can affect creditworthiness. Moreover, the following article has strong literature review in order to identify and summarize the main factors of the creditworthiness of oil-producing countries. Although, there is not strong empirical research, the study is based on the statistical world data.